2018
DOI: 10.1039/c8nr05492d
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced luminescence and energy transfer in Mn2+ doped CsPbCl3−xBrx perovskite nanocrystals

Abstract: The enhanced luminescence of Mn2+ in Mn2+:CsPbCl3−xBrx NCs is related to Br composition-dependent energy transfer from excitons to Mn2+.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
38
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(42 citation statements)
references
References 43 publications
3
38
1
Order By: Relevance
“…Cs-oleate precursors and CsPbCl 3 NCs were synthesized following our previous reports. 26,27 In a typical procedure for the synthesis of Fe 2+ doped CsPbCl 3 NCs, PbCl 2 (1Àx mmol) and FeCl 2 (x mmol) were mixed with OLA (1.5 mL), OA (1.5 mL), TOP (1 mL), and ODE (10 mL) in a 50 mL three-neck round-bottomed ask. The reaction mixture was degassed at 110 C for 20 min, and then heated up to 170 C under an argon ow.…”
Section: Methodsmentioning
confidence: 99%
“…Cs-oleate precursors and CsPbCl 3 NCs were synthesized following our previous reports. 26,27 In a typical procedure for the synthesis of Fe 2+ doped CsPbCl 3 NCs, PbCl 2 (1Àx mmol) and FeCl 2 (x mmol) were mixed with OLA (1.5 mL), OA (1.5 mL), TOP (1 mL), and ODE (10 mL) in a 50 mL three-neck round-bottomed ask. The reaction mixture was degassed at 110 C for 20 min, and then heated up to 170 C under an argon ow.…”
Section: Methodsmentioning
confidence: 99%
“…11 Additionally, Mn 2+ doping was also reported with CsPbBr 3 , CsPbCl 3Àx Br x and CsPbI 3 inorganic perovskite QDs by different groups. 12,13 On the other hand, no reports are found on Pb substituted HPQDs and most of the studies were found on MAPbBr 3 QDs due to their high stability and PLQY. The rst solution based HPQDs were fabricated by the Pérez-Prieto group in 2014 with a PLQY of 20%.…”
Section: Introductionmentioning
confidence: 99%
“…4f, the lifetime of band gap transition decreases continuously with the increase of Mn 2+ concentration. The lifetime decreases to 4.682 ns at x=0.20 compared with that at x=0.01 (5.448 ns), suggesting the energy transfer exists between the host and Mn 2+ [14,[36][37][38]. It is confused to explain that the lifetime of Mn 2+ decreases with the increase of Mn 2+ concentration.…”
Section: Resultsmentioning
confidence: 94%